Implementation of new electricity regulatory norms for deviation settlement mechanism: A case study of India. Issue 1 (1st January 2019) - Gupta, Manju; Gupta, Sushma; Thakur, Tripta
Abstract: In this research paper, an innovative solution by proposing a novel mechanism for implementation of regulatory approach—based new deviation settlement scheme for frequency control is suggested. Power systems of many developing countries have to face sustained generation deficiency, large frequency fluctuations and are susceptible to even small disturbance. Operating such a system is a difficult task and innovative solutions are needed to solve this situation. To overcome this situation, India has adopted commercial mechanism known as Availability-based Tariff (ABT), which has a component linked with frequency. A commercial mechanism is a paradigm shift in the operational strategies from the conventional frequency control to new deviation control. This proposed scheme satisfies Central Electricity Regulatory Commission (CERC) criteria and inclusive future norms. The MATLAB used to enable to analyze proposed rules and the strength of the approach, is to segregate the conventional Automatic Generation Control (AGC) with new UI-based AGC. The enhancement of AGC algorithms is to meet increased demand by efficient implementation of algorithm for generators rescheduling, as per new CERC norms.